AGAMA DI TENGAH KONFLIK SOSIAL: Tinjauan Sosiologis Atas Potensi Konflik Keberagaman Agama di Masyarakat - Nur Kafid (UIN Raden Mas Said Surakarta, 2015)
The study aims to describe public perception about thereality of religious diversity, with the main focus on the dynamic andprocess of emerging religious‟ sentiment in the daily lives. The existenceof non-Islamic religious believers within Muslim majority community,have always getting serious concern, from their religious activities up totheir social relations. The attitude of tolerance were still resided on thehuman relation level, and were not touched yet on the awareness levelabout the essence of the religious diversities‟ itself. As its consequences,various friction and restlessness were always emerged and causeddisharmony relation among them. Furthermore, various prejudices werealways rising that any social activities done by them (non-Islamicbeliever) have assessed as part of their effort of Christianization.